International Organizations Intervention In The Syrian Conflict Through Chemical Weapons Violation - Eska Dwipayana Pulungan (PERSPEKTIF, 2023)
This paper aims to answer why chemical weapons such as Sarin and Chlorine are used as a primary basis of International Organizations to carry out the humanitarian intervention in the Syrian conflict. In this case, the humanitarian approach related to freedom from fear echoed by Galtung further elaborated with International Organizations Theory. Based on an investigation conducted by an International Organization, namely, the United Nations, found not only Bashar Al-Assad's regime used chemical weapons but also the opposition. However, the scale and intensity of their use were different. Instead of targeting the enemy using chemical weapons, the primarily affected victims are civilians who indicated support the opposition and vice versa. International organizations then tried to negotiate with Assad's regime, the often party uses chemical weapons, and also the opposition to avoid using chemical weapons. Next followed by the Organization for the Prohibition of Chemical Weapons, which opened humanitarian diplomacy with Assad's regime and the opposition to stop using chemical weapons. Cooperation between the United Nations and the Organization for the Prohibition of Chemical Weapons has successfully suppressed chemical weapons use by imposing international sanctions. However, sometimes the vetoes of allies allied with the Assad regime have the effect to imposing sanction on Assad's regime.